Balancing harm and harmony: Evolutionary dynamics between gut microbiota-derived flagellin and TLR5-mediated host immunity and metabolism - Boram Seo; Mi Young Lim (Virulence)
The gut microbiota maintains host health and shapes immune responses through intricate host-microbe interactions. Bacterial flagellin, a key microbe-associated molecular pattern, is recognized by Toll-like receptor 5 (TLR5) and NOD-like receptor family caspase activation and recruitment domain-containing 4 inflammasome. This dual recognition maintains the delicate balance between immune tolerance and activation, thereby influencing health and disease outcomes. Therefore, we explored the structural and functional evolution of bacterial flagellin to elucidate its role in innate and adaptive immune responses, along with its impact on metabolic processes, particularly via TLR5. In this review, we highlight the diagnostic and therapeutic potential of flagellin, including its application in vaccine development, cancer immunotherapy, and microbiome-based therapies. We integrated perspectives from structural biology, immunology, and microbiome research to elucidate the co-evolutionary dynamics between gut microbiota-derived flagellin and host immunity. Our interpretations provide a basis for the development of innovative strategies to improve health and disease management.